Crosstalk between sphingolipids and vitamin D3: potential role in the nervous system. (24th February 2017) - Garcia‐Gil, Mercedes; Pierucci, Federica; Vestri, Ambra; Meacci, Elisabetta
Abstract : Sphingolipids are both structural and bioactive compounds. In particular, ceramide and sphingosine 1‐phosphate regulate cell fate, inflammation and excitability. 1‐α, 25‐dihydroxyvitamin D3 (1, 25(OH)2 D3 ) is known to play an important physiological role in growth and differentiation in a variety of cell types, including neural cells, through genomic actions mediated by its specific receptor, and non‐genomic effects that result in the activation of specific signalling pathways. 1, 25(OH)2 D3 and sphingolipids, in particular sphingosine 1‐phosphate, share many common effectors, including calcium regulation, growth factors and inflammatory cytokines, but it is still not known whether they can act synergistically. Alterations in the signalling and concentrations of sphingolipids and 1, 25(OH)2 D3 have been found in neurodegenerative diseases and fingolimod, a structural analogue of sphingosine, has been approved for the treatment of multiple sclerosis. This review, after a brief description of the role of sphingolipids and 1, 25(OH)2 D3, will focus on the potential crosstalk between sphingolipids and 1, 25(OH)2 D3 in neural cells.